Performance of health workers in implementing the healthy Indonesia application - Mutiara Miftahul Jannah; Firdawati Firdawati; Rinang Mariko; Yuniar Lestari; Afdal Afdal; Eka Nofita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: My Healthy Indonesia Application is a cornerstone of Indonesia's health system digital transformation, designed to streamline vaccination recording and reporting. However, its implementation at community health centers in Padang City faces challenges, marked by data discrepancies and suboptimal vaccination coverage. Purpose: To identify healthcare worker performance in implementing the healthy Indonesia application. Method: A mixed-methods study was conducted in five Community Health Center in Padang City. The quantitative phase employed a cross-sectional design with total sampling of 127 health workers. Data were collected using validated questionnaires and analyzed using chi-square and multivariate logistic regression. The qualitative phase involved in-depth interviews with 13 key informants, analyzed using thematic analysis. This study investigates factors associated with health workers' performance in using My Healthy Indonesia Application and explores underlying reasons behind these challenges. Results: Quantitative analysis revealed that motivation (p=0.014), leadership (p=0.018), and workload (p=0.009) were significantly associated with performance, with motivation as the most dominant factor (OR 0.254; p=0.011). Knowledge (p=0.602) was not significantly associated. Qualitative findings generated seven themes: complex motivational dynamics dominated by professional responsibility; significant infrastructure limitations (reliance on personal devices/internet); persistent application bugs (data loss, duplication); increased administrative workload; a digital generation gap; adaptive strategies (time management, team collaboration); and a clear recommendation for a single, integrated application. Conclusion: Health worker performance in using My Healthy Indonesia Application presents a paradox: good performance persists despite significant systemic barriers, primarily driven by strong intrinsic motivation. However, this reliance on individual resilience is unsustainable. Improving My Healthy Indonesia Application effectiveness requires holistic interventions addressing technical issues, reducing workload, bridging the digital divide, and nurturing the professional dedication of health workers.